Effect of Nutrition Interventions on Knowledge and Adoption Feasibility of Gluten Free Products by Celiac Disease Patients (Indian Journal of Extension Education, 2022)
The study was undertaken with the objective to improve the nutritional knowledge and technical skill of celiac disease patients. Since celiac is a disease which occurs due to gluten allergy and quite prevalent these days. Hence this study was planned to promote nutrition education to celiac patients and give them training on preparation of gluten free products during 2020-21. Thirty celiac disease patients were selected randomly using snowball method. Lectures cum demonstrations for preparation of gluten free quinoa based laddoo, upma, porridge and pulao were given. Leaflets containing the recipes for preparation and nutritional importance of quinoa products were distributed. Pre exposure scores (1.00 to 1.55) depicted that respondents had very less knowledge of celiac disease, its causes, gluten free foods, quinoa and its products, price of quinoa, nutritional importance and medicinal uses of quinoa seeds. A significant increase (P<0.01) was observed in knowledge scores (1.71 to 2.00) of respondents after imparting nutrition education. All the quinoa products i.e. laddoo, porridge, pulao and upma were liked by them and they felt that they can easily make these products.